Innovation and internationalisation: Is there a connection with entry modes and destination countries? [abstract] - Santos-Pereira, Carla (2022)
In a globalized world where internationalisation plays a crucial role for the success of companies, innovation is also proving to be a key strategic decision for their development and competitiveness. Despite the broad consensus on the growing importance of internationalization and innovation for companies, some questions arise: Is there a link between innovation and internationalization? Does the relationship between internationalisation and innovation differ according to entry modes? Does the importance of innovation differ between destination markets? Taking into account a sample of Portuguese companies, this study seeks to answer mainly the last two questions. Thus, the goal is to explore whether it is possible to establish a pattern of relationship between internationalisation modes, destination markets and innovation for Portuguese firms. To achieve the objectives, we set out to accomplish in this work, we used data gathered through an online questionnaire survey. A questionnaire was designed and sent by email to 8183 companies from the AICEP database. From the data collected we gathered 310 valid responses, which were then processed by IBM SPSS Statistics 27.0 software. Quantitative Analysis were used and given the nature of the data (categorical variables measured on a nominal or ordinal scale), the statistical methods used were Exploratory Analysis (Univariate and Multivariate Exploratory Factorial Analysis- EFA) and Inferential Analysis (Correlation analysis: Spearman´s correlation and Chi-square test, and Mann-Whitney nonparametric test). According to the results, we can find empirical evidence that are indeed the companies with internationalisation modes that require greater commitment, as well as with geographically and psychologically more distant destination markets, the ones that attach greater importance to innovation as a determinant of internationalisation.